Preparation and Characterization of Novel Magnetic ZnFe2O4–Hydroxyapatite Core–Shell Nanocomposite and Its Use as Fixed Bed Column System for Removal of Oil Residue in Oily Wastewater Samples - Heba H. El-Maghrabi; Rasha Hosny; Mahmoud Ramzi; M.A. Zayed; Mahmoud Fathy (Egyptian Journal of Petroleum)
Using magnetic nanoparticles to remove the dispersed oil from produced water is a promising way to overcome the difficulties faced by current treatment technologies. Therefore, in this study, novel ZnFe2O4-hydroxyapatite core-shell nanocomposites (ZFHA) was prepared by precipitation method and investigated as an adsorbent to remove residual oil from produced wastewater. The prepared ZFHA nanocomposites were studied by FTIR, X-ray diffraction, HRTEM, SAED, and EDX. The results revealed that hydroxyapatite was coated on the ZnFe2O4 surface and formed a core-shell structure. The effect of various parameters on oil adsorption process like bed height (59, 118 and 178 mm), flow rate (1, 3 and 5 mL min−1), effect of temperature 25–77 °C, initial oil concentration (100, 500, 1000 and 10,000 ppm) and pH (2–10) were investigated. The experimental data showed that with increased column bed depth from 59 to 178 mm, breakpoint time (tb) increased from 30 to 48 min. The highest equilibrium adsorption capacity of oil at optimum conditions (77 °C, 10,000 ppm, 3 mL/min and 178 mm) were estimated to be 3500 mg L−1. The contact time decreased with the increase of bed height and flow rate. Adsorption kinetic was evaluated in a fixed bed column. Finally, the regeneration of the exhausted ZFHA adsorbent was assessed; which revealed satisfactory results for three times reusability after saturation. Therefore; ZFHA could be applied effectively for adsorption of residual oil from synthesis oily wastewater samples prepared from produced water of Egyptian fields of the petroleum industry. Keywords: Magnetic ZnFe2O4-hydroxyapatite, Core-shell nanocomposite, Oil adsorption, Oily wastewater, Adsorption kinetics